Evaluation of a new rapid-diagnostic test for peritonitis in peritoneal dialysis: the PERIPLEX® device. - Pierre-Yves Durand; Christian Verger (RDPLF, 2020)
In 2017, the British company MOLOGIC developed a new rapid-diagnostic test (PERIPLEX®) for the diagnosis of peritonitis in patients undergoing peritoneal dialysis. This single-use test is based on the detection in dialysate of two biomarkers of bacterial infection: Interleukin-6 (IL-6) and matrix metalloproteinase-8 (MMP-8). The test was evaluated in a prospective multicenter study including 10 centers from the RDPLF (French Language Peritoneal Dialysis Registry). A total of 184 tests were performed; 86 tests were negative and 98 were positive. 85 peritonitis were confirmed. There were no false-negatives, and 13 false-positives. Of the 13 false-positives, 7 of them were for sepsis without peritonitis, or peritoneal inflammation. The performance of the test is considered excellent: sensitivity 100%, specificity 86.9%, positive predictive value 86.7%, negative predictive value 100%. In this study, a negative test can formally rule out the diagnosis of peritonitis.